Keterampilan Berbicara Bahasa Jerman dengan Model Pembelajaran Kooperatif Tipe Jigsaw - Ainun, Ainun; A.P, Jufri; Saleh, Nurming (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This type of research is a classroom action research that aims to determine the improvement of German speaking skills in class XI students of SMA Negeri 14 Makassar by using the jigsaw type cooperative learning model. This research consists of two cycles where each cycle consists of two meetings that have the same flow of planning, implementation, observation, and reflection. The data from this study were analyzed using the Mix Method, where the data obtained will be presented in qualitative form describing student learning outcomes and quantitative data which is the result of the German speaking skills test given at the third meeting of each cycle. Based on the results of data analysis, the average score obtained by students in cycle I was 61.91 and in cycle II the average score obtained by students was 84.85. From the results of the study, it is concluded that the jigsaw type cooperative learning model can help improve students' German speaking skillsKeywords: Model, Cooperative, Jigsaw, Speaking Skill, German